Water Use Behavior, Learning, and Adaptation to Future Change in Urban Gardens - Egerer, Monika H.; Lin, Brenda B.; Philpott, Stacy M. (Frontiers in Sustainable Food Systems, 2018)
Urban agriculture is undergoing a contemporary global renaissance, providing fresh food for growing urban populations and vital environmental benefits for cities. Despite urban agriculture's social-environmental importance, a rural bias in agricultural research has left critical gaps in our understanding of how urban agroecosystem management can sustainably produce food in the future. Specifically, there is a need to study urban agriculture water management due to recent drought events, likely increases in urban water scarcity, and higher temperatures. Gardeners can play a decisive role in increasing urban agriculture's sustainability through their water, soil, and vegetation management. Here, we examined water use, vegetation, and soil management in the California Central Coast—a region facing drought—to better understand how urban agriculture management affects water use sustainability. We worked with gardeners to study their water management decisions using citizen science, where volunteer gardeners collected their own water use behavior data and participated in a survey to describe their behaviors around water use, water conservation, and plot level management. We found that water use varies by gardener, and water use is positively related to mulching and crop cover in plots. Contrary to expectations, gardeners that reported high levels of concern over current environmental conditions (drought) and water conservation in the survey tended to use high amounts of water, suggesting that environmental worldviews do not necessarily translate into everyday practices. On the other hand, gardeners in gardens with more rules and regulations around water use tended to use less water, highlighting the practicality of enforcing rules and regulations during drought periods. Gardeners reported interest in adapting gardening practices to more sustainably use water regardless of their current practices. The combination of education and rules and regulations will help improve the sustainability of garden systems in times of environmental change.